Efficient Modulation of Electrocatalyst Interfaces by Atomic Layer Deposition: Fundamentals to Application. Issue 7 (28th April 2022) - Wu, Fan; Zhou, Ling; Guo, Daying; Xi, Bin
Abstract : Under the scope of "carbon neutrality" and "emissions peak, " renewable energy technologies and systems relying on electrocatalytic reactions (e.g., oxygen evolution reaction (OER), oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), and carbon dioxide reduction reaction (CO2 RR)), though kinetically slow, are attractive. To promote the efficiency of such systems, engineering of the electrocatalyst interface is an effective strategy. In the fabrication toolbox for complex surface/interface, the advanced atomic‐layer deposition (ALD) technique is superior to conventional methods, evidenced by precise control of thickness, composition, uniformity, etc. This review summarizes recent developments in ALD implementation in a variety of electrocatalytic systems, especially the electrode interface preparation and modulation. Beyond all doubt, the introduction of the ALD process could dramatically increase the number of electrocatalytic‐active sites and hence improve the performance. However, its practical application in this field is open to deliberation, while process cost and complexity are in consideration. Abstract : Advanced atomic‐layer deposition (ALD) is considered a promising technique for surface and interface engineering in competitive electrocatalysis systems. Accordingly, this review sorts out facile ALD manipulation in such a field and demonstrates representative progress. Moreover, applications of the design strategies for renewable energy are anticipated.